Current prevalence of self-monitoring of blood pressure during pregnancy: the BUMP Survey - Tucker, KL; Hodgkinson, J; Wilson, H; Crawford, C; Stevens, R; Lay-Flurrie, S; Dale, M; Astbury, N; Chappell, LC; McManus, R (Lippincott, Williams & Wilkins, 2021)
OBJECTIVE: To understand the current prevalence of, and attitudes to, self-monitoring of blood pressure (BP) during pregnancy.